Egg Shell powder reinforced Polypropylene (PP) composite: Effect of mechanical and heat capacity - Shaymaa H. Jasim; Wisam Alhassan; Ziyad T. Almalki (Al-Qadisiyah Journal of Pure Science, 2020)
The mechanical properties of Polypropylene (PP): Egg Shell powder composite was assessed with respect to the effect of filler content shells powder Egg varying from 1% to 10% by weight of the composite. Apparent amelioration in the mechanical parameters has recorded best ratios 5% and 7% weight. The mechanical properties of prepared film have examined through diverse parameters concerning the elastic deformity based on calculated the load – elongation properties. The conduct of the stress - strain curve was investigated in terms of the cold drawing model. The elastic behavior decreased at 5% composite Egg Shell powder. The specific heat capacity of Polypropylene, obvious an increase of the composite specific heat capacity using egg shell content.